Morphometric Study of Age-related Changes of the Spinal Cord - Sasaki, Akinori; Takasaki, Masaru; Yamada, Shigeo; Mukai, Masami; Ezaki, Yukiyoshi; Mizutani, Toshio (Nihon Rōnen Igakkai zasshi, 1994)
The relation of aging to the length of the spinal cord and to the cross-sectional area at the levels of C6 and L3 of the spinal cord was studied in 140 autopsy cases who between the age of 47 to 105 without spinal cord lesions. In addition the effect of being bed-ridden on the spinal cord was studied in 11 of 140 cases. As pathological controls, we referred to 40 autopsy cases with compression change of the cervical cord. The length of the spinal cord had no correlation with aging but had a significant positive correlation with the height of the subject. A significant decrease in the cross-sectional area of the spinal cord was observed after the age of 80, in particular at C6. However, the extent of the decrease was not as serious as that of pathological control cases. Decrease of cross-sectional area was associated with that of white matter area. In addition, effect of being bed-ridden on the spinal cord was reflected in a significant decrease of the grey matter of the lumbar cord.